Murder on black swan lane ebook - Penrose, Andrea (Wrexford & Sloane Mystery, 2017)
In Regency London, an unconventional scientist and a fearless female artist team up to trap a cold-hearted killer: "Thoroughly enjoyable" (Deanna Raybourn, New York Times –bestselling author). The Earl of Wrexford possesses a brilliant scientific mind, but boredom and pride lead him to reckless behavior. So when pompous, pious Reverend Josiah Holworthy publicly condemns him for debauchery, Wrexford unsheathes his rapier-sharp wit and strikes back. As their war of words escalates, London's most popular satirical cartoonist, A.J. Quill, skewers them both. But then the clergyman is found slain in a church—his face burned by chemicals, his throat slashed ear to ear—and Wrexford finds himself the chief suspect. An artist in her own right, Charlotte Sloane has secretly slipped into the persona of her late husband, using his nom de plume, A.J. Quill. When Wrexford discovers her true identity, she fears it will be her undoing. But he has a proposal—use her sources to unveil the clergyman's clandestine involvement in questionable scientific practices, and unmask the real murderer. Soon Lord Wrexford and the mysterious Mrs. Sloane plunge into a dangerous shadow world hidden among London's intellectual enclaves to trap a cunning adversary—before they fall victim to the next experiment in villainy . . . "Sharp, engaging characters, rich period detail, and a compellingly twisty plot, Andrea Penrose delivers a winner." —Deanna Raybourn, New York Times –bestselling author "Fans of C.S. Harris take note! A riveting ride through Regency London, from the slums of St. Giles, to the mansions of Mayfair." —Lauren Willig, New York Times –bestselling author "Historical chemistry meets alchemy . . . A delight of a book.&rdquo